Breaking the cycle: how poverty affects children’s oral health in developing nations—a rapid review - Setiawan, Arlette Suzy; Indriyanti, Ratna; Sukmasari, Susi (Frontiers in Public Health, 2025)
BackgroundOral diseases remain a significant public health challenge worldwide, disproportionately impacting children in developing countries due to socioeconomic hardship and limited healthcare access.PurposeThis rapid review evaluates the relationship between low household income and children’s oral health outcomes in developing countries.MethodWe followed PRISMA 2020 and Cochrane Rapid Review guidelines. A systematic search of five databases (2012–2022) using refined keywords identified eligible studies. Quality assessment used the NIH tool.ResultsOf 1,574 articles identified, 13 met inclusion criteria. Most were cross-sectional studies from China, India, Nigeria, Brazil, and Syria. A consistent association was found between lower socioeconomic status and worse oral health outcomes, including higher DMFT/dmft scores, gingivitis, and early childhood caries (ECC).ConclusionLow socioeconomic status (SES) is associated with worse oral health outcomes in children in developing countries.